Islamic Marketing and Branding - T. C. Melewar, S. F. Syed Alwi (2019)
Islamic Marketing and Branding: Theory and Practice provides a concise mix of theory, primary research findings and practice that will engender confidence in both students and practitioners alike by means of the case study included in each chapter.